Responding to a shadow banking crisis: The lessons of 1763 - Stephen Quinn; William Roberds (Federal Reserve Bank of Atlanta, 2012)
In August 1763, northern Europe experienced a financial crisis with numerous parallels to the 2008 Lehman Brothers episode. The 1763 crisis was sparked by the failure of a major provider of acceptance loans, a form of securitized credit resembling modern asset-backed commercial paper. The central bank at the hub of the crisis, the Bank of Amsterdam, responded by broadening the range of acceptable collateral for its repo transactions. Analysis of archival data shows that this emergency source of liquidity helped to contain the effects of the crisis, by preventing the collapse of at least two other major securitizers. While the underlying themes seem to have changed little in 250 years, the modest scope of the 1763 liquidity intervention, together with the lightly regulated nature of the eighteenth century financial landscape, provide some informative contrasts with events of late 2008.
Keywords: E58; G01; G21; N21; 330; shadow banks; central banks; liquidity